Integrating Wordwall and Talking Stick: An Innovative Strategy to Boost Motivation and Learning Outcomes in Senior High School - Aisyah, Nur; Suwadji (Universitas Islam Raden Rahmat Malang, 2025)
Abstrak: One of the primary challenges faced by educators is how to effectively motivate students to develop a genuine interest in what they are learning, which in turn significantly influences their academic performance. A strategic approach to address this issue involves the use of appropriate and contextually relevant instructional media that align with students’ learning needs. This study seeks to offer a novel perspective on enhancing student motivation and learning outcomes by integrating Wordwall interactive media with the Talking Stick method in a comprehensive instructional framework. Employing a quasi-experimental design with nonequivalent control groups, the study examines the effectiveness of this integrated approach. The findings indicate that students in the experimental group exhibited notable improvements in both academic achievement and motivational indices. Statistical analysis using SPSS revealed a non-significant difference in learning outcomes (Asymp. Sig. (2-tailed) = 1.000, p > 0.05), while a significant difference was observed in motivation levels, as indicated by Levene’s test (p = 0.000, p < 0.05), suggesting a substantial impact on students’ motivational engagement. These results underscore the pedagogical potential of combining Wordwall interactive media with the Talking Stick method to effectively enhance both motivation and academic performance among eleventh-grade students in Islamic Religious Education, particularly in topics related to tolerance and the preservation of human life.